bacterial fungal isolates from lower respiratory tract infections (LRTLs) in adult Iraqi leukaemic patients - Al-Neaimy, mohammed; Al-Salloum, Khalida M.; Al-salloum, Suhaila (Journal of the Faculty of Medicine Baghdad, 2006)
Background: